The Impact of Learning Management Systems (LMS) on University Students' Language Skills - Sarwadi, Sarwadi; Huda, Sayaiful; Mujtahidin , Mujtahidin; Rahman, Bohri (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
The use of Learning Management System (LMS) has become an important part in supporting learning in higher education. The main problem underlying this research is the limited understanding of the impact of LMS on the development of students' language skills, especially at the higher education level. This study aims to explore the impact of LMS on the development of students' language skills. Qualitative research methods with a case study approach are used to deeply understand the experiences of students and lecturers in using LMS. By triangulating data collected from observations, interviews, and document analysis, this study attempts to present a comprehensive picture of the implementation of LMS in language education. The data obtained in this study were analyzed thematically. The results of the study indicate that LMS features such as discussion forums, collaborative assignments, and automatic feedback contribute significantly to improving students' writing, speaking, and reading skills. In conclusion, LMS plays an important role in supporting the development of language skills, but the optimization of the use of these features needs to be considered. This study is expected to provide insight for teachers and LMS developers in creating more effective learning strategies.